Social Marketing Comes of Age: A Brief History of the Community of Practice, Profession, and Related Associations, With Recommendations for Future Growth. (September 2019) - Kassirer, Jay; Lefebvre, Craig; Morgan, Winthrop; Russell-Bennett, Rebekah; Gordon, Ross; French, Jeff; Suggs, L. Suzanne; Lee, Nancy; Biroscak, Brian J.
The emergence of the International Social Marketing Association (iSMA) and its affiliated regional associations is a key indicator that social marketing is maturing, both as a community of practice and as a profession. Through these associations, the international social marketing community has developed a consensus definition of the discipline and a consensus list of basic competencies for social marketing certificate programs. The associations are currently working on certification programs and a code of ethics. Continued movement toward professionalization can help social marketers be recognized and valued more highly for their relevant skills, knowledge, expertise, trustworthiness and altruism. At the same time, the discipline must address a number of key challenges and opportunities, to stay relevant and thrive.